Charge-Trapping Non-Volatile Memories : Volume 2--Emerging Materials and Structures - Dimitrakis, Panagiotis (Springer International Publishing : Imprint: Springer, 2017)
This book describes the technology of charge-trapping non-volatile memories and their uses. The authors explain the device physics of each device architecture and provide a concrete description of the materials involved and the fundamental properties of the technology. Modern material properties, used as charge-trapping layers, for new applications are introduced. Provides a comprehensive overview of the technology for charge-trapping non-volatile memories; Details new architectures and current modeling concepts for non-volatile memory devices; Focuses on conduction through multi-layer gate dielectrics stacks.